When baseball went white : reconstruction, reconciliation, and dreams of a national pastime - Swanson, Ryan A. (University of Nebraska Press, 2014)
"Explains how in the decade following the Civil War, baseball became segregated because its leaders wanted to grow its presence and appeal to Southerners, and wanted to professionalize it. The result was the exclusion of black players that lasted until 1947"--